THE ROLE OF INTERNATIONAL EXPERIENCES IN THE DEVELOPMENT OF AGROTURISM IN UZBEKISTAN - Jalilov Shokhjahon Kholbozor oglu (Modern American Journals, 2025)
This article describes the tourism industry, its role in the economy of the country, as well as agritourism, which is one of the main directions of the tourism industry, its history, stages of development and international experience. The main features and models of agritourism are listed. Models of agritourism and their peculiarities are shown. The current state of the agro-tourism industry around the world has been analyzed. It describes the work being done and to be done for the development of agritourism around the world. The problems facing the development of agritourism in Uzbekistan and recommendations for their solutions are presented.
Keywords: Agritourism, rural tourism, domestic tourism, ecological tourism, eno-tourism (wine tourism), ethno-tourism, culinary tourism, geotourism, farming, tourism and tourist services on organic farms (WWOOF).